PENGARUH IMBANGAN UBI JALAR UNGU Var. TELO CEMORO, TEPUNG TERIGU DAN TEPUNG TAPIOKA TERHADAP KARAKTERISTIK STICK UBI JALAR UNGU - F. S. Octaviani; Hendrawan; Kelik Putranto (Ma'soem University, 2021)
The rind and flesh of purple sweet potato (Ipomea batatas L.) is deep purple that give impression to consumer, besides this sweet potato contain carbohydrate, vitamin and antioxidant. A way to utilize purple sweet potato is as raw material in making stick of purple sweet potato. The objective of the research was to determine the right ratio to produce the best stick characteristic of purple sweet potato. The experimental method was applied in this research with randomize block design. The result of the research showed that the ratio of purple sweet potato, wheat flour and tapioca flour 50:10:40 produced stick with lowest water content, the high carbohydrate content, the best flavor and taste. The ratio of 60:10:30 produced the best texture and color.